Identifikasi Karakteristik Morfologis dan Hubungan Kekerabatan pada Tanaman Jahe (Zingiber officinale Rosc.) di Desa Dolok Saribu Kabupaten Simalungun - Indah Aryanti,; Eva Sartini Bayu; Emmy Harso Kardhinata (Universitas Sumatera Utara, 2015)
The objective of research was to identify morphological characteristics and phylogenetic relationships of ginger at Simalungun District, Dolok Saribu village of Dolok Pardamea. The research was conducted from July to September 2014 by using descriptive method consists of 15 samples. The result showed that there were two types of ginger : large white ginger and red ginger. The qualitative character were five identical and five different morphological characters and the quantitative character was obtained four narrow and six wide morphological characters. The closest phylogenetic relationships are samples A4 (large white ginger) with A9 (large white ginger) with coefficient of distance value is 2.723, meanwhile the farthest phylogenetic relationships are samples A1 (large white ginger) with A11 (red ginger) with coefficient of distance value is 36.598. The result of dendogram showed at scale 5 was formed 10 groups, scale 10 was formed 5 groups, scale 15 was formed 4 groups, scale 20 was formed 3 groups and scale 25 was formed 2 groups. Group 1 consists of large white ginger and group 2 consists of red ginger. Phylogenetic relationships between ginger plants at Dolok Saribu village of Simalungun District still have a close level relationships.Keywords : Identification, ginger, morphology